A psychoanalytic study of Theodore Decker's trauma in Donna Tartt's The Goldfinch - Muhammad Rijal Aziz; Ambar Andayani (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2026)
This study examines the psychological trauma experienced by Theodore Decker, the protagonist of Donna Tartt's Pulitzer Prize-winning novel The Goldfinch (2013). Using Sigmund Freud's psychoanalytic theory as the primary framework, the research identifies the causes of Theodore's trauma, examines its effects on his behavior and psychological condition, and analyzes the defense mechanisms he employs in response to his traumatic experiences. This study applies a descriptive qualitative method, with the novel serving as the primary data source; data were collected through close reading and note-taking and analyzed by interpreting narrative passages that relate to Theodore's psychological condition. The findings show that Theodore's trauma originates from the death of his mother in a museum bombing, the bombing itself, abandonment by his father, and the resulting loss of stability and security. These experiences produce lasting psychological effects, including repressed memory, repetition compulsion, unresolved loss, and a gradually developing self-awareness. To cope with this suffering, Theodore relies on unconscious defense mechanisms, namely repression, denial, displacement, projection, and regression, alongside an emerging capacity for self-awareness and acceptance. The study concludes that trauma in the novel functions not as a temporary reaction but as an ongoing psychological process, and that partial healing becomes possible through growing self-understanding and meaningful human connection.